Formalno izobraževanje medicinskih sester v Sloveniji - Kvas, Andreja (Obzornik zdravstvene nege, 2003)
In the frames of research study on nurses in Slovenia in 2001, the author was especially interested in the degree of formal education of nurses and their aspirations for broader knowledge in the field of nursing care. An inquiry comprising 104 questions was send by mail to 2450 nurses from all over Slovenia with different degrees of education. The results show that formal as well as informal forms of education should be available which would also enhance the quality of nursing care.
Keywords: ankete; education; Education, Nursing; health care; izobraževanje; Izobraževanje, zdravstvena nega; medicinske sestre; Questionnaires; Slovenia; Slovenija; zdravstvo